Improving Elderly’s Dental Hygiene Through Nursing Home Staff’s Dental Health Education at the Nursing Home (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Stomatitis often occurs in elderly at nursing home. They need nursing home staff assistance to maintain their dental and oral health. Therefore, nursing home staff need dental health education. Lecture or discussion methods, which are more effective to improve knowledge, attitude and skill of nursing home staff was the purpose of this research. The research design was quasi-experiment research and pretest-posttest with control group. The sample was 42 nursing home staffs and 74 elderlies, divided into two groups, consisted of 18 nursing home staffs and 33 elderlies using lecture method. Another group consisted of 24 nursing home staffs and 41 elderlies using discussion method.  Validity was tested with product moment. Questionnaire of knowledge, attitude and skill correlation was 0.4725 – 0.6853; 0.4772–0.6962 and 0.3100–0.4916. Reliability test with Alpha Cronbach was 0.9292; 0.9273; 0.792. Research result was lecture and discussion methods were effective to improve knowledge, attitude and skill of nursing home staff to increase elderly’s dental hygiene. The research concludes that discussion method is effective to improve knowledge while lecture is more effective to improve attitude and skill of nursing home staff.